A Flexible Organic Single Crystal with Plastic‐Twisting and Elastic‐Bending Capabilities and Polarization‐Rotation Function. Issue 31 (25th May 2020) - Liu, Huapeng; Lu, Zhuoqun; Tang, Baolei; Qu, Cheng; Zhang, Zuolun; Zhang, Hongyu
Abstract: Flexible organic single crystals capable of plastic or elastic deformations have a variety of potential applications. Although the integration of plasticity and elasticity in a crystal is theoretically possible and it may cause rich and complex deformations which are highly demanded for potential applications, the integration is hard to realize in practice. Here, we show that through utilizing different modes of external forces for influencing molecular packing in different crystallographic directions, plastic helical twisting and elastic bending can both be achieved for a crystal, and they can even be realized simultaneously. Detailed crystallographic analyses and contrast experiments disclose the mechanisms behind these two kinds of distinct deformations and their mutual compatibility. Based on the plastically twistable nature of the crystal, a new application field of flexible organic single crystals, namely polarization rotators, is successfully opened up. Abstract : Twist and shout : The integration of plastic twisting and elastic bending in an organic single crystal is achieved. By controlling the twisting degree of the crystal, the polarization direction of light can also be controlled quantitatively and easily. Thus, a new application field of flexible organic single crystals, that is, polarization rotators, is opened up.